Analisis Pengaruh Growth Opportunity dan Good Corporate Governance terhadap Nilai Perusahaan - Baiq Nirsya Mutayassara (Fakultas Ekonomi dan Bisnis Islam, 2022)
This study aims to analyze the effect of growth opportunity and good corporate governance on company value (Study in the Consumer Goods Industry Sub-sector Food & Beverage which is included in the 2014-2018 Indonesia Sharia Stock Index). The type of data used in this study is quantitative data with secondary data sources, data collection techniques with observation and sampling techniques in this study is purposive sampling. The selected population is 18 food and beverage companies listed on the Indonesia Stock Exchange in the period 2014-2018 with a sample of 8 companies that fit the criteria that the authors have determined. To analyze this research the writer uses Panel Data Analysis Test with the help of Eviews 9 application. The results of this study indicate that growth opportunity proxied by asset growth has a negative and not significant effect on firm value, and good corporate governance represented by the audit committee and managerial ownership has a positive and not significant effect on firm value while good corporate governance with institutional ownership has a negative effect. and not significant to the company's value.